Analisis Kelayakan Investasi Dendeng Daging Sapi (Studi Kasus di PD “Carole Jaya”) - Milana, Lia; Whydiantoro, Whydiantoro (Jurnal Riset Bisnis dan Investasi, 2018)
Beef trading industry in Indonesia is growing, both in terms of quantity and quality lead to the emergence of intense competition, therefore every trading company is required to be creative in the face of business competition in order to meet and satisfy the needs and desires of consumers. One way is through product development. One way is through product development. Product development is an important thing for a company to maintain its existence or at least can guarantee the survival of the company. It is also encouraging PD Carole Jaya which is engaged in beef and mutton trade, to create a new innovation that is the development of beef products by making beef jerky, as an alternative in the development of beef products and to increase sales productivity for maintaining the existence of its business. But of course, in the development of this product, should consider the investment plan, whether worthy or not product development is done, given the amount of capital required for the manufacture of this jerky. In the development of this product, there are three stages of the activities undertaken: preparation, execution (manufacturing process) and final stage. In the final stage of the activities undertaken is to process data, analyze the results of research and make conclusions. In this financial data processing using financial feasibility analysis tool with PayBack Period method, ARR (Average Rate of Return), NPV (Net Present Value), IRR (Internal Rate of Return) and (R / C Ratio) Business Efficiency and BEP (Break Event Point). The results of the investment analysis show that the PBP (Payback Period) of this investment is 3 months, ARR (Average Rate of Return) of 1.35%, NPV (Net Present Value) generated 27.998.634, - which means when NPV> 1, then the feasible investment, PI (Profitability Index) of 1.35 means that the investment can be run (Feasible), R / C Ratio of 1.35 means is, this investment is very efficient and profitable and BEP (production) of Rp. 258,500, - and BEP (unit) of 44.4 kg. Thus, the product development effort by making beef jerky is feasible to be implemented by PD. Carole Jaya.